Electronic Democracy - Kersting, Norbert (Verlag Barbara Budrich, 2012)
The timely book takes stock of the state of the art and future of electronic democracy, exploring the history and potential of e-democracy in global perspective. Analysing the digital divide, the role of the internet as a tool for political mobilisation, internet Voting and Voting Advice Applications, and other phenomena, this volume critically engages with the hope for more transparency and political participation through e-democracy.